Soils, land and food : - Wild, Allan (Cambridge University Press, 2002)
Unlike Malthus, Wild (emeritus, soil science, U. of Reading) is optimistic that food production can meet increasing population demands. After reviewing the history of agriculture, he provides a data-based assessment of the key natural resources for sustainable land and soil management, and case studies of raising yields in developing regions.